The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.1002/etep.1613
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of inductances of a salient pole synchronous machine under different axial eccentricity conditions

Abstract: SUMMARY Different radial eccentricities in salient pole machine are well documented in previous studies. In reality, the most probable case is the rotor eccentricity, which is not uniform down the axial length. This article determines a precise model of salient pole synchronous machine for general axial eccentricity condition. Proposed model allows calculating salient pole machine inductances with different static, dynamic, and mixed axial eccentricities in a unified technique. By taking into account machine g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…The WFM is mostly adopted for a healthy machines whose air gap is symmetrical or uniform [3,15]. The MWFM is largely adopted for faulty machines since it accounts for air gap eccentricity [5,17,18]. The work of [29] revealed that Modified Winding Function Theory (MWFTh) is generally accepted in analyzing rotating electrical machines which have a very small air gap.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The WFM is mostly adopted for a healthy machines whose air gap is symmetrical or uniform [3,15]. The MWFM is largely adopted for faulty machines since it accounts for air gap eccentricity [5,17,18]. The work of [29] revealed that Modified Winding Function Theory (MWFTh) is generally accepted in analyzing rotating electrical machines which have a very small air gap.…”
Section: Introductionmentioning
confidence: 99%
“…Majority of the researchers who investigated faulty machines patronized this method. The calculations of inductances of salient-pole synchronous motor operating under eccentricity using MWFTh were done by [17,20] and [21]. Again [21] developed an analytical model that can compute the machine inductances under any kind of eccentricity.…”
Section: Introductionmentioning
confidence: 99%
“…Detection of the eccentricity fault in induction machines and synchronous generators has been the subject of many papers. New machines and drives need more precise, quick, and easy fault diagnosis methods, so mechanical faults such as eccentricity fault and magnetic faults such as demagnetization fault in permanent‐magnet (PM) machines have been widely studied in order to find more accurate and simpler diagnosis methods.…”
Section: Introductionmentioning
confidence: 99%
“…The introduced approach uses standard statistical analyses like mean, variance, and information entropy, on one phase of the steady-state current signal provided by the VSD, together with sensorless synchronous speed estimation from the stator voltage supply, as inputs to an ANN for classifying the induction motor operational condition, different from reviewed literature, where a direct connection of the motor to the power supply is considered for simplicity and improved certainty of the used approach during the fault detection process. The introduced technique is able to detect distinct faults like BRB, misalignment (MAL), and unbalance (UNB) at different rotating speed, unlike previous approaches that detect just one single fault as bearings [6][7][8], rotor bars [9][10][11][12][13], and UNB [14][15][16][17][18] at a fixed rotating speed. Previous methods in reviewed literature use computationally complex signal processing techniques like WT [19][20][21][22][23], FT [24][25][26][27], and their combination with other techniques [28][29][30][31][32][33][34][35][36][37] for detecting multiple faults, which restrain them to off-line applications.…”
Section: Introductionmentioning
confidence: 99%
“…Differently, in , unbalance in induction generators is detected by using the ratio of active power to apparent power (power factor) as a condition monitoring criterion. The effects of axial eccentricities, as rotor asymmetries, on the machine inductances are studied in . The effects on rotor vibrations of design, manufacturing, and external factors, like mechanical unbalance, are presented and discussed in .…”
Section: Introductionmentioning
confidence: 99%